Adapting to Democratic Norms: Party Financing Regulations in Indonesia and Germany Compared - Arif, Mohammad; Mamonto, Moch Andry Wikra Wardhana (Journal of Law, Politic and Humanities, 2024)
This study conducts a comparative analysis of party financing regulations in Indonesia and Germany to explore how these countries adapt to democratic norms, with an emphasis on the impact of regulatory frameworks on political party financing. By investigating diverse socio-political landscapes and historical contexts, this research aims to identify a convergence towards democratic norms, significantly influenced by the regulations governing political party financing. Employing normative legal research, utilizing legislative, conceptual, case, and comparative approaches, analyzed through qualitative descriptive methods, this study integrates document analysis and case studies to provide a comprehensive understanding of the regulatory frameworks. The findings indicate that although Indonesia and Germany are both committed to enhancing democratic governance through transparent and accountable party financing, the implementation of these regulations faces significant challenges. In Indonesia, these include limited enforcement mechanisms, a lack of comprehensive audits, and difficulties in tracking the sources of political donations. Conversely, Germany’s structured approach to party financing regulation demonstrates a robust enforcement mechanism and a public funding model, yet it also encounters challenges, particularly in the realm of indirect support and the use of third-party entities. This study contributes to the discourse on strengthening democratic institutions and practices by offering a comparative perspective that highlights the importance of strong and adaptable regulatory frameworks to ensure transparency, accountability, and fair competition in political financing.